Diagnostic Accuracy of Multidetector Computed Tomography Using Functional Endoscopic Sinus Surgery Protocol for the Evaluation of Fungal Sinusitis, with Histopathology as the Gold Standard - Shehzad Karim Bhatti, Zunair Maqsood, Irum Shahzad, Sana Zaheer Qureshi, Nancy Dhakal, Sadia Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Fungal sinusitis is an increasingly acknowledged illness characterized by a diverse array of clinical manifestations, ranging from non-invasive to potentially fatal invasive forms. A correct diagnosis as soon as possible is important to help with the right treatment and avoid problems. Multidetector computed tomography (MDCT) employing the Functional Endoscopic Sinus Surgery (FESS) procedure is important in assessing paranasal sinus disorders; however, its diagnostic precision in fungal sinusitis necessitates additional validation through histopathological comparison. Objective:To determine the diagnostic accuracy of multidetector computed tomography using the FESS protocol in diagnosing fungal sinusitis, keeping histopathology as the gold standard. Methodology: This cross-sectional study took place in the Department of Radiology at Govt. Kot Khawaja Saeed Hospital in Lahore over a span of three months. We used non-probability convenient sampling to include 65 individuals between the ages of 14 and 80 who were clinically suspected of having paranasal sinusitis. All patients had an MDCT scan done using the FESS procedure. Imaging results were documented and juxtaposed with histological findings acquired post-surgical intervention. We used SPSS version 25 to look at the data. We figured out the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy. Results: The average age of the patients was 50.29 years, with 61.54% of them being men. CT scans showed fungal sinusitis in 58% of patients, and histology confirmed it in 60%. MDCT showed a sensitivity of 84.62%, a specificity of 80.77%, a positive predictive value of 86.84%, a negative predictive value of 77.78%, and an overall diagnostic accuracy of 83.08%. Mucosal thickening with hyperdensity (100%), sinus expansion (89.23%), and bony erosion (81.54%) were all common CT findings. Conclusion: MDCT with the FESS protocol is a dependable and efficient imaging technique for diagnosing fungal sinusitis. It not only gives very accurate diagnoses, but it also assists with disease characterisation and surgical planning when combined with clinical and histological data. Keywords: Fungal sinusitis, multidetector computed tomography, FESS protocol, diagnostic accuracy, histopathology